Sources of community livelihoods and economic losses due to conflict with the Sumatran Tiger (Panthera tigris sumatrae) in the buffer area of Batang Gadis National Park - Fahma, Nurul; Patana, Pindi (Talenta Publisher, 2023)
The existence of people living around the buffer zone in recent times has led to negative interactions in the form of conflicts between humans and wild animals, one of which is with the Sumatran tiger. The purpose of this study was to identify the sources of livelihood for the community in the buffer area of the Batang Gadis National Park (BGNP), and calculate the total economic losses suffered by the community due to human and wildlife conflicts in the buffer area of the national park. This study used a survey method, data were collected through interviews with selected respondents based on purposive sampling method with snowball technique. Data analysis is done by descriptive analysis. The results of the research show that the source of livelihood for the people living around the TNBG area is mostly farmers. The community's perception of the disturbance of wild animals and Sumatran tigers in Hutabaringin Julu Village and Bangkelang Village is that some people consider wild animals or Sumatran tigers to be beneficial to them in the balance of nature, and some others consider wild animals to be no useful in life because they are considered to disturb community plantation lands. The tiger conflict caused an economic loss of IDR 14,400,000 in Hutabaringin Julu Village and Bangkelang Village of IDR 35,280,000.